2022
DOI: 10.1071/cp21486
|View full text |Cite
|
Sign up to set email alerts
|

Biochar actions for the mitigation of plant abiotic stress

Abstract: Abiotic stresses are the dominant constraints to successful crop production in the modern era. Over the past few decades, researchers have devised various techniques to ease the effects of abiotic stresses on crop plants. Biochar is a vital eco-friendly biostimulant that mostly increases crop production and alleviates the adverse effects of different abiotic stresses. It improves crop yield as a fertiliser and soil quality as a soil conditioner. Biochar amendment in the soil is gaining popularity these days. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 143 publications
4
18
0
Order By: Relevance
“…BC is a carbon-rich organic substance with a porous structure, a wide surface area, and a high ion exchange ability that improves the physical qualities of agricultural soil [ 83 , 84 ]. A number of studies found that BC application improves the different physio-biochemical processes such as photosynthesis, hormonal and enzymatic activity in plants and decreases the harmful effects of salt stress on plants ( Figure 1 and Table 2 , [ 5 , 22 , 83 , 84 , 85 ]).…”
Section: Organic Amendments For Salinity Stress Mitigationmentioning
confidence: 99%
See 3 more Smart Citations
“…BC is a carbon-rich organic substance with a porous structure, a wide surface area, and a high ion exchange ability that improves the physical qualities of agricultural soil [ 83 , 84 ]. A number of studies found that BC application improves the different physio-biochemical processes such as photosynthesis, hormonal and enzymatic activity in plants and decreases the harmful effects of salt stress on plants ( Figure 1 and Table 2 , [ 5 , 22 , 83 , 84 , 85 ]).…”
Section: Organic Amendments For Salinity Stress Mitigationmentioning
confidence: 99%
“…Soil salinity is a key abiotic stress that interferes with crop growth, development, and yield through altering morphological, physio-biochemical, and molecular processes [ 1 , 2 , 3 , 4 , 5 , 6 ]. Every year, 1–2% of cultivable land is reduced due to soil salinity and worldwide, about 800 million hectares (23%) of total arable lands are affected by soil salinity [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This Special Issue has also selected articles on how biochar and fertiliser can increase soil health and crop yields and overcome soil constraints such as acidity, salinity, drought, low fertility and remediation of contaminated soils. Imran et al (2022) wrote a review paper stating that biochar is a soil conditioner and an eco-friendly biostimulant that mainly increases crop productivity, alleviates adverse effects of abiotic stresses and improves crop yield. Biochar amendment is gaining popularity because it improves soil's physiochemical and biological properties.…”
Section: Introductionmentioning
confidence: 99%